2018
DOI: 10.1080/14658011.2018.1532672
|View full text |Cite
|
Sign up to set email alerts
|

Physical and morphological characterisation of poly(L-lactide) acid-based electrospun fibrous structures: tunning solution properties

Abstract: Poly(l-lactide) nano/micro fibres were produced using the electrospinning technique. The influence of solvent type and solution concentration on the morphology and structure of electrospun fibres were investigated. For this purpose, the electrospinning was performed using 2, 2, 2-trifluoroethanol (TFE) or dichloromethane (DCM) solvents at solution concentrations in a range of 5-9 wt-%. Morphological studies showed that versus DCMbased fibres with beaded structures and porous surface, when using TFE as a solven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…Depending on the characteristics of the PLA solutions, the process parameters and ambient conditions, the diameter and morphology of the PLA fibers produced by electrospinning will differ. As an example, in research works performed by Maleki et al the influence of the solvent system on the electrospinning of PLLA fibers is investigated [57,66]. The results demonstrated that the dielectric constant and vapor pressure of the solvent are important parameters, which significantly affect the fiber morphology, diameter, and crystallinity and hence influence the mechanical properties of the fibrous structures.…”
Section: Application Of Pla-based Electrospun Fibers In Wound Healingmentioning
confidence: 99%
See 3 more Smart Citations
“…Depending on the characteristics of the PLA solutions, the process parameters and ambient conditions, the diameter and morphology of the PLA fibers produced by electrospinning will differ. As an example, in research works performed by Maleki et al the influence of the solvent system on the electrospinning of PLLA fibers is investigated [57,66]. The results demonstrated that the dielectric constant and vapor pressure of the solvent are important parameters, which significantly affect the fiber morphology, diameter, and crystallinity and hence influence the mechanical properties of the fibrous structures.…”
Section: Application Of Pla-based Electrospun Fibers In Wound Healingmentioning
confidence: 99%
“…Solvents with a low vapor pressure like 2,2,2-trifluoroethanol (TFE) provided enough time for crystals to grow during fiber formation resulting in a high crystallinity. Solutions obtained from chloroform with lower conductivity caused less stretching of the charged jet in the electrostatic field and resulted in larger diameters of fibers [57,66]. In another study by Maleki et al, in order to investigate the effect of solvent type on the mechanical properties of electrospun PLLA structures, a double nozzle electrospinning set-up was used to fabricate continuous twisted yarns from PLLA fibers.…”
Section: Application Of Pla-based Electrospun Fibers In Wound Healingmentioning
confidence: 99%
See 2 more Smart Citations
“…The properties of nanofibers are significantly affected by various processing parameters, such as the instrumental conditions (applied voltage, flow rate, and distance to the collector), polymer solution properties (viscosity, surface tension, conductivity, and solvent polarity), and the ambient conditions (temperature and humidity) (Maleki, Semnani Rahbar, Saadatmand, & Barani, 2018; Rostami et al., 2019).…”
Section: Properties Of Electrospun Nanofibersmentioning
confidence: 99%